A Small Change With a Twist Ending: A Single Residue in EGF-CFC Drives Bilaterian Asymmetry. (20th December 2022) - Truchado-García, Marta; Perry, Kimberly J; Cavodeassi, Florencia; Kenny, Nathan J; Henry, Jonathan Q; Grande, Cristina
Abstract: Asymmetries are essential for proper organization and function of organ systems. Genetic studies in bilaterians have shown signaling through the Nodal/Smad2 pathway plays a key, conserved role in the establishment of body asymmetries. Although the main molecular players in the network for the establishment of left-right asymmetry (LRA) have been deeply described in deuterostomes, little is known about the regulation of Nodal signaling in spiralians. Here, we identified orthologs of the egf-cfc gene, a master regulator of the Nodal pathway in vertebrates, in several invertebrate species, which includes the first evidence of its presence in non-deuterostomes. Our functional experiments indicate that despite being present, egf-cfc does not play a role in the establishment of LRA in gastropods. However, experiments in zebrafish suggest that a single amino acid mutation in the egf-cfc gene in at least the common ancestor of chordates was the necessary step to induce a gain of function in LRA regulation. This study shows that the egf-cfc gene likely appeared in the ancestors of deuterostomes and "protostomes", before being adopted as a mechanism to regulate the Nodal pathway and the establishment of LRA in some lineages of deuterostomes.